Cadmium Chalcogenide (CdS, CdSe, CdTe) Quantum Dots for Solar‐to‐Fuel Conversion. Issue 11 (17th July 2022) - Xiang, Xianglin; Wang, Linxi; Zhang, Jianjun; Cheng, Bei; Yu, Jiaguo; Macyk, Wojciech
Abstract : Photocatalysis is considered a promising technology to alleviate the pressure of environmental pollution and energy shortage. Among various photocatalysts, cadmium chalcogenide quantum dots (CdX QDs) stand out due to their excellent visible light absorption ability and efficient charge separation properties. This review presents the atomic and electronic structures of CdX QDs and their synthetic strategies. In addition, the reaction mechanism of CdX QDs in photocatalytic solar‐to‐fuel conversion is discussed. Another focus of this review is the optimization strategies for CdX QDs to improve their photocatalytic performance. Finally, the challenges and the perspectives on CdX QDs are briefly proposed. Abstract : This review presents the atomic and electronic structures of cadmium chalcogenide quantum dots (CdX QDs) and their synthetic strategies. The reaction mechanism of CdX QDs in photocatalytic solar‐to‐fuel conversion is discussed. Another focus of this review is the optimization strategies for CdX QDs to improve their photocatalytic performance. Finally, the challenges and the perspectives on CdX QDs are briefly proposed.